DENSITAS DAN AKTIVITAS AYAM HUTAN MERAH (Gallus gallus) DI HUTAN GUNUNG KLABAT, MINAHASA UTARA, SULAWESI UTARA - Puasa, Marton; Saroyo, Saroyo; Wahyudi, Lalu (UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTRed jungle fowl is one of the important animals that live in the forest and has various roles, such as ecological, economic and aesthetic functions. This study aims to analyze the population of red jungle fowl in forest habitat I and forest habitat II in the forest of Mount Klabat Utara Minahasa and analyze the activity of red forest chicken in forest habitat I and forest habitat II in the forests of Mount Klabat North Minahasa. This study uses a survey method with line transect sampling. Transects were determined as many as four, namely two transects in forest habitat type I and two transects in forest habitat type II. Each transect length is 2000 m and the left width is 20 m and the right width is 20 m, each transect is observed for 10 times. Density found in transect I was 25.63 animals / km² and transect II was 10.63 animals / km², in addition it was found that the dominant activity in both types of forest was forest I with feeding activity 19 (0.76%) moved 4 (0.16%), rest 2 (0.20%), in forest II looking for food, 5 (0.50%), move 3 (0.30%), rest 2 (0.20%).Keywords: Red jungle fowl (Gallus gallus), density, activity, Mount Klabat, North Minahasa, North Sulawesi ABSTRAKAyam hutan merah merupakan salah satu satwa penting yang hidup di hutan dan mempunyai berbagai peran, seperti fungsi ekologi, ekonomi dan estetika. Penelitian ini bertujuan menganalisis populasi ayam hutan merah pada habitat hutan I dan habitat hutan II di hutan Gunung Klabat Minahasa Utara dan menganalisis aktivitas ayam hutan merah pada habitat hutan I dan habitat hutan II di hutan Gunung Klabat Minahasa Utara. Penelitian ini menggunakan metode survei dengan sampling berbentuk transek garis. Transek ditentukan sebanyak empat, yaitu dua transek pada tipe habitat hutan I dan dua transek pada tipe habitat hutan II. Panjang transek masing-masing ialah 2000 m dan lebar kiri 20 m dan lebar kanan 20m, setiap transek dilakukan pengamatan selama 10 kali. Densitas yang di temukan pada transek I yaitu 25.63 ekor/km² dan di transek II 10.63 ekor/km², selain itu di temukan aktivitas yang dominan pada kedua tipe hutan yaitu hutan I dengan aktivitas makan 19 (0.76%) berpindah 4 (0.16%), istirahat 2 (0.20%), di hutan II mencari makan, 5 (0.50%), berpindah 3 (0.30%), istirahat 2 (0.20%).Kata kunci: Ayam hutan merah (Gallus gallus), densitas, aktivitas, Gunung Klabat, Minahasa Utara, Sulawesi Utara